Incidental Phaeochromocytoma on Staging PET-CT in a Patient with a Sigmoid Tumour and Situs Inversalis Totalis. (8th July 2014) - Boland, M. R.; Lowery, A. J.; Walsh, S.; Beddy, D.; Prichard, R. S.; O'Shea, D.; Skehan, S. J.; McDermott, E. W.
Abstract : An adrenal "incidentaloma" is defined as an unexpected finding on radiological imaging performed for unrelated indications. Improvements in radiological technology have seen a dramatic increase in this phenomenon. We report the unique case of a 60-year-old female presenting with a 6-month history of abdominal pain, altered bowel habit, and rectal bleeding. Her past medical history included situs inversus totalis and a patent ductus arteriosus. Colonoscopy revealed an ulcerated tumour in her sigmoid colon. Staging PET-CT confirmed a sigmoid tumour and also identified a large heterogenous enhancing FDG-avid right adrenal mass. Biochemical testing/MIBG imaging confirmed a right adrenal phaeochromocytoma. Hypertension was controlled and excision was performed via a transperitoneal laparoscopic adrenalectomy, in the left lateral decubitus position. Uniquely, liver retraction was not required due to its position in the left hypochondrium. Histology confirmed a benign 46 mm phaeochromocytoma. Subsequent uncomplicated sigmoid colectomy/right salpingo-oophorectomy for a locally advanced colonic tumour was performed with adjuvant chemotherapy. This case highlights the importance of accurately identifying functioning adrenal tumours before elective surgery as undiagnosed phaeochromocytomas carry significant intraoperative morbidity/mortality. Right adrenalectomy was made easier in this patient by the liver's unique position. Uncomplicated colorectal resection was made possible by combined preoperative functional/anatomical imaging.